Prevalence and factors of sleep problems among Japanese children: a population-based study - Kuki, Asami; Terui, Ai; Sakamoto, Yui; Osato, Ayako; Mikami, Tamaki; Nakamura, Kazuhiko; Saito, Manabu (Frontiers in Pediatrics, 2024)
Background: High prevalence of sleep problems in not only children with neurodevelopmental disorders (NDS) but also non NDS has been established. However, there are few studies that have looked into population-based and age-specific prevalence of sleep problems of children. Moreover, there are even fewer studies that have investigated the correlation of demographic and lifestyle-related factors affecting sleep problems in children. Considering these, the purpose of this study is to assess the correlation of the prevalence of sleep problems and selected socio-demographic and lifestyle-related factors in 5-year-old Japanese children in population-based study. Methods: Study children (SC) were recruited from two cohorts of the Hirosaki City 5-Year-Old Child Developmental Health Checkup Study.The first cohort consisted of 281 (162 males, 119 females) children recruited from 2014 to 2015, and the second cohort consisted of 2055 (1,068 males, 987 females) children from 2018 to 2019. In total there were 2,336 SC participants (1,230 males and 1,106 females). To determine the prevalence of sleep problems the Japanese Sleep Questionnaire for Preschoolers (JSQ-P) was utilized, and sleep problems are defined by a total score of ≥86. To determine socio-demographic and lifestyle-related factors affecting sleep, 10 factors (NDS diagnosis, birth month, childcare place, income, number of siblings, bedtime, waking time, sleeping hours, sleep onset delay, and screen time) were selected. Finally, to determine the correlation between prevalence of sleep problems and the selected demographic and lifestyle-related factors, data was analyzed using chi-square test. Results: The prevalence rate of sleep problems in 5-year-olds was 18%(369/2055). Further, the prevalence of sleep problems was high in participants with ASD(50.4%), ADHD(39.8%), <2 million yen of income(30.5%), no siblings(24.2%), >22:00 of bedtime(30.7%), >7:30 of waking time(30.7%), < 9 hours of sleeping hours(25.3%), >30 minutes of sleep onset delay(35.3%), and ≥2 hours of screen time(21.1%). Conclusion: The findings report 18% prevalence rate of sleep problems in 5-year-old children. Further, the findings establish a significant correlation of sleep problems and NDS, specific socio-demographic, and lifestyle-related factors. In considering the identified modifiable lifestyle-related factors contributing to sleep problems among the participants (i.e., bed/waking times and screen times), sleep programs to address these concerns are suggested.